Investigation of the thermal and moisture regime of cold attics using an instrumental method - Filonenko, Olena; Filipets, Maksym; Berun, Denys (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article presents the results of an experimental study of the thermal and humidity regime of a cold attic using modern measuring instruments. The relevance of studying the microclimatic parameters of the attic space is substantiated in view of their critical role in ensuring the durability and safe operation of buildings. The dynamics of temperature and humidity changes in a cold attic in different periods of time is analyzed. Based on the results of the study, practical recommendations for optimizing the microclimate in the attic space aimed at preventing the formation of condensation, mold, and structural deformations are formulated.
Keywords: thermal and humidity conditions; cold attic; microclimate; logger; moisture meter